Combination of steroid with azathioprine in treatment of giant cell autoimmune hepatitis - Eroğlu, Yasemen; Düzovalı, Öznur; Kavukçu, Salih; İrken, Gülersu; Büyükgebiz, Benal (The Turkish Journal of Pediatrics, 1997)
Giant cell hepatitis is a rare disorder after the newborn period. Drugs, autoimmunity, and viruses (lately, paramyxovirus infection) have been implicated in its etiology. Without treatment, liver dysfunction is progressive and fatal. Immunosuppression with steroids and azathioprine has been demonstrated to sustain improvement in the disease. In this report, a one-year-old boy who has giant cell hepatitis with Coombs' positive hemolytic anemia and anti-smooth muscle antibodies is presented, and the course of the disease and the patient's response to treatment with steroid and azathioprine is reviewed.
Keywords: giant cell hepatitis; autoimmune hemolytic anemia; steroid and azathioprine therapy